Kearifan Lokal yang Responsif Gender dalam Legenda Asal Mula Tanaman Padi di Sumba - Kelen, Konradus Doni; Nusa, Silvester (Ideas Publishing, 2024)
This research starts from situation and phenomenon that is unfair to the social position of women which has been held hostage by a patriarchal culture. The aim of this research is to show the local wisdom that is gender responsive to build gender awareness in creating justice for women. The method used in this research is ethnography with a qualitative descriptive approach. The results of this research show that the legend of the origin of the rice plant in Sumba is a moral story that is aware and fair to gender. The data in this research was obtained from interviews. The results of this research can be used as evaluation material for the people of Sumba so that discrimination against women is no longer permitted.